Stronger and tougher nanosized dense ceria-doped tetragonal zirconia polycrystals by sinter-HIP. Issue 5 (May 2023) - Zhao, Ruoshi; Liu, Xintong; Li, Hezhen; Song, Lu; Ma, Jing
Abstract: Ceria-doped tetragonal zirconia polycrystal (Ce-TZP) ceramics possess significant toughness and aging resistance, while their strength is relatively limited due to the high tendency of grain growth, which has long hindered their versatile applications. This work demonstrates an effective method to combine stereolithography with pre-sintering and hot isostatic pressing (HIP) to obtain dense Ce-TZP ceramics with a reduced grain size of about 420 nm. In addition to the contribution of smaller grains, the Ce-rich phase Ce0.75 Zr0.25 O2 precipitates at the grain boundaries during HIP hinders grain growth and strengthens the grain boundaries, together leads to a transgranular-dominant fracture mode. As a result, the achieved Ce-TZP ceramic simultaneously reaches a high flexural strength of 770.90 ± 76.06 MPa and an excellent fracture toughness of 11.96 ± 1.31 MPa·m 1/2, which are 48% and 29% higher, respectively, compared to the pressureless-sintered samples. This method is expected to enable broader applications of pure Ce-TZP ceramics and to be further extended for designing and manufacturing densified and fine-grained components with complex structures. Highlights: Densified pure Ce-TZP ceramics with nanograins of about 420 nm is successfully achieved without introducing other dopants. High strength of 770.90 ± 76.06 MPa and high toughness of 11.96 ± 1.31 MPa·m 1/2 are simultaneously achieved in pure Ce-TZP. The combination of stereolithography and sinter-HIP can be a universal way for dense, nanosized oxide ceramic parts design.